1997
DOI: 10.1002/(sici)1097-0142(19970201)79:3<538::aid-cncr16>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Erectile functioning of men treated for prostate carcinoma

Abstract: RESULTS. The probability of maintaining erectile functioning after radiotherapy is 0.69. The probability after surgery is 0.42. This difference is significant. Analysis of 3 Academic Computing Services, The University the effects of variables such as patient age and stage of disease on erectile functionof Calgary, Calgary, Alberta, Canada.ing could not be performed due to inconsistencies across studies and the limited number of studies reporting such variables. CONCLUSIONS.The published data indicate that men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…A meta-analysis (Robinson, Dufour, & Fung, 1997) of 40 studies showed that the likelihood of erectile dysfunction is .58 after prostatectomy and .31 after radiotherapy. Longitudinal studies (e.g., Lubeck et al, 1999) have shown that urinary problems generally subside within a year after treatment, whereas sexual problems tend to persist.…”
Section: Prostate Cancer and Qolmentioning
confidence: 99%
“…A meta-analysis (Robinson, Dufour, & Fung, 1997) of 40 studies showed that the likelihood of erectile dysfunction is .58 after prostatectomy and .31 after radiotherapy. Longitudinal studies (e.g., Lubeck et al, 1999) have shown that urinary problems generally subside within a year after treatment, whereas sexual problems tend to persist.…”
Section: Prostate Cancer and Qolmentioning
confidence: 99%
“…58 Reported potency rates after EBRT and RP have varied widely from 2% to 86% of men following RT 59 -62 and 14% to 82% following RP. 31,63,64 This variance may be attributable to the limitations of physician reported outcome assessment, differences in patient populations, variation in time points relative to treatment at which potency is evaluated and the multiplicity of potency definitions used in contemporary studies. 65 We analyzed scores on the sexual function and bother domains of the PCI, comparing men who would be classified as potent or impotent based on the objective criterion of erections greater than 50% of the time when desired, and/or vaginal or anal intercourse at least 1 time in the prior 4 CONTEMPORARY PROSTATE CANCER MANAGEMENT IN UNITED STATES weeks, a definition best approximating the National Institutes of Health Consensus definition of impotence.…”
Section: Quality Of Life National Outcomesmentioning
confidence: 99%
“…12 Other data indicate that men with normal erectile function are more likely to retain this function after radiotherapy than after radical prostatectomy. 13 Testosterone appears to be necessary for the maintenance of libido in both men and women. 14 Drugs which signi®cantly decrease testosterone synthesis or block utilization have been associated with decreased libido.…”
Section: Figurementioning
confidence: 99%